2009
DOI: 10.3354/meps08299
|View full text |Cite
|
Sign up to set email alerts
|

Growth validation of gold coral Gerardia sp. in the Hawaiian Archipelago

Abstract: Colonies of the Hawaiian gold coral Gerardia sp. (n = 48) were measured, marked and then revisited 1 to 9 yr later to look for evidence of linear growth. The video images showed no change in the proportional size of the coral colonies relative to the marker pots left on the bottom and no change in the pattern of distal branches. Few of the measured delta values exceeded the error of our measurement technique, and the detected change in the sample was statistically indistinguishable from zero. Even though the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The gold coral colony marked in the 2000 study (Parrish & Roark 2009) and then found toppled but alive in 2007 was half dead when it was revisited 5 yr later in 2012. Most of the underside polyps were absent, but since the coral toppled sometime between 5 and 12 yr earlier, it shows that the rates of tissue die-off can be slow.…”
Section: Toppled Colonies and Remnants Of The Hostmentioning
confidence: 99%
See 3 more Smart Citations
“…The gold coral colony marked in the 2000 study (Parrish & Roark 2009) and then found toppled but alive in 2007 was half dead when it was revisited 5 yr later in 2012. Most of the underside polyps were absent, but since the coral toppled sometime between 5 and 12 yr earlier, it shows that the rates of tissue die-off can be slow.…”
Section: Toppled Colonies and Remnants Of The Hostmentioning
confidence: 99%
“…A live gold coral colony marked standing in 2000 as part of a prior growth study (Parrish & Roark 2009) was revisited in 2007 and found toppled but fully alive. Left in place, it was revisited 5 yr later in 2012 to document any changes in its condition.…”
Section: Toppled Gold Coral Skeletonsmentioning
confidence: 99%
See 2 more Smart Citations
“…is the zo anthid Gerardia sp. (lifespan in the order of millennia with growth rates as low as 5 µm yr −1 : Druffel et al 1995, Parrish & Roark 2009). …”
Section: Radiocarbon Datingmentioning
confidence: 99%